2018
DOI: 10.3389/fmicb.2018.01340
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Curli in Soil-Persistent Escherichia coli Is Mediated by a C-di-GMP Signaling Defect and Suggests Evidence of Biofilm-Independent Niche Specialization

Abstract: Escherichia coli is commonly viewed as a gastrointestinal commensal or pathogen although an increasing body of evidence suggests that it can persist in non-host environments as well. Curli are a major component of biofilm in many enteric bacteria including E. coli and are important for adherence to different biotic and abiotic surfaces. In this study we investigated curli production in a unique collection of soil-persistent E. coli isolates and examined the role of curli formation in environmental persistence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Curli promotes biofilm adhesion to abiotic surfaces or cells and contributes to persistence in hosts. 30 Cellulose promotes delayed bacterial clearance. 31 We found that the majority of E. coli ST1193 and ST131 possessed no curli/no cellulose in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Curli promotes biofilm adhesion to abiotic surfaces or cells and contributes to persistence in hosts. 30 Cellulose promotes delayed bacterial clearance. 31 We found that the majority of E. coli ST1193 and ST131 possessed no curli/no cellulose in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium and S. Senftenberg adhere efficiently to fruits and vegetables, while others like S. Arizona, S. Agona and S. Heidelberg do not attach well to fruits and vegetables [50,51]. of Salmonella [55][56][57]. Biofilms are formed by cellular matrix which has been consistently found to be created by curli and cellulose [58].…”
Section: Fruits and Vegetables As Vectors Of Transmission Of Salmonellamentioning
confidence: 99%